Development of the Career Anchors Scale among Occupational Health Nurses in Japan. Issue 6 (29th November 2016) - Kubo, Yoshiko; Hatono, Yoko; Kubo, Tomohide; Shimamoto, Satoko; Nakatani, Junko; Burgel, Barbara J.
Abstract : Objectives: This study aimed to develop the Career Anchors Scale among Occupational Health Nurses (CASOHN) and evaluate its reliability and validity. Methods: Scale items were developed through a qualitative inductive analysis of interview data, and items were revised following an examination of content validity by experts and occupational health nurses (OHNs), resulting in a provisional scale of 41 items. A total of 745 OHNs (response rate 45.2%) affiliated with the Japan Society for Occupational Health participated in the self‐administered questionnaire survey. Results: Two items were deleted based on item‐total correlations. Factor analysis was then conducted on the remaining 39 items to examine construct validity. An exploratory factor analysis with a main factor method and promax rotation resulted in the extraction of six factors. The variance contribution ratios of the six factors were 37.45, 7.01, 5.86, 4.95, 4.16, and 3.19%. The cumulative contribution ratio was 62.62%. The factors were named as follows: Demonstrating expertise and considering position in work (Factor 1); Management skills for effective work (Factor 2); Supporting health improvement in groups and organizations (Factor 3); Providing employee‐focused support (Factor 4); Collaborating with occupational health team members and personnel (Factor 5); and Compatibility of work and private life (Factor 6). The confidence coefficient determined by the split‐half method was 0.85. Cronbach's alpha coefficient for the overall scale was 0.95, whereas those of the six subscales were 0.88, 0.90, 0.91, 0.80, 0.85, and 0.79, respectively. Conclusions: CASOHN was found to be valid and reliable for measuring career anchors among OHNs in Japan.